Appropriate diagnostic technology in the management of cardiovascular diseases : report of a WHO Expert Committee, meeting held in Geneva from 23 to 30 November 1987 - WHO Expert Committee on Appropriate Diagnostic Technology in the Management of Cardiovascular Diseases; World Health Organization (Geneva : World Health Organization, 1988)
An authoritative guide to the uses and limitations of currently available technologies for the diagnosis, assessment, and management of cardiovascular diseases. Authored by a group of 19 international experts, the report concentrates on factors that can help gauge the appropriateness of specific technologies, ranging from the simple to the highly sophisticated, in a diversity of different clinical settings. Throughout, emphasis is placed on the importance of taking a realistic look at both the needs of patients and the demands on resources when attempting to match the promise of a technology with the reality of costs and long-range performance. The main part of the report provides a guide to 15 different cardiovascular diagnostic and evaluative technologies. For each, readers are given a concise explanation of the technology, its clinical applications, the sensitivity and specificity of information yielded, safety, costs of the equipment, costs of disposables, vulnerability to breakdown, costs of replacement parts, and the types of skilled manpower and facilities required to use the equipment effectively
1. Introduction -- 2. General considerations -- 3. Specific cardiovascular diagnostic and evaluative technologies -- 4. special issues -- 5. availability of diagnostic technology at various levels of health care -- 6. Conclusions and recommendations -- Acknowledgements -- Bibliography
Keywords: Cardiovascular Diseases; Medical Informatics; Noncommunicable Diseases